Atlas obscura : an explorer's guide to the world's hidden wonders - Foer, Joshua; Thuras, Dylan; Morton, Ella (Workman Publishing, 2019)
This second edition takes readers to even more curious and unusual destinations, with over one hundred new places, dozens and dozens of new photographs, and two very special features: twelve city guides, covering Berlin, Budapest, Buenos Aires, Cairo, London, Los Angeles, Mexico City, Moscow, New York City, Paris, Shanghai, and Tokyo. And a three-panel gatefold with a full-color map augmented by an around-the-world travel itinerary. More a cabinet of curiosities than traditional guidebook, Atlas Obscura revels in the unexpected, the overlooked, the bizarre, and the mysterious."--Dust jacket flap.